Ecstasies in Protestant Europe Around 1700: Bodily Convulsions and Religious Dissent - von Tippelskirch, Xenia (Reformation, 2025)
In the early modern period, physical symptoms were frequently interpreted as markers of religious affiliation. This article examines ecstatic states from this period, focusing on those interpreted by physicians and theologians as signs of divine intervention, possession, disease, or simulation. It specifically explores the prophetic utterances and physical manifestations of the so-called petits prophètes in the French Dauphiné, reported during the intensification of Huguenot persecution in the late seventeenth century. These phenomena sparked a range of contemporary responses, particularly in Protestant circles in Lausanne, Geneva, and Rotterdam, where debates over their credibility raged. Catholics also participated, often ridiculing the events. In the context of confessional polemics, bodily signs were used as proof of authenticity, yet their validity was continually contested.